What factors enable the production of a high profile LGBT assembly and facilitate a culture more accepting of LGBT students at The BRIT School? - Offen, Michael (2012)
This ethnographic study explores both what is present and what is absent at The BRIT School for Performing Arts and Technology to allow a high profile LGBT assembly and a more accepting culture for LGBT students. The research is framed around historic and modern discourses of sexuality, including Section 28, its impact on schools and the legacy it has left behind. Unlike the existing literature that finds schools to be unsupportive environments for LGBT students and teachers, this study finds that The BRIT School has a unique set of factors enabling it to offer a more accepting and supportive environment. Largely through qualitative analysis of students’ experiences and perceptions, findings reveal that liberal discourses of sexuality operate within the school, supported by relationships between staff and students, and a supportive LGBT curriculum. In addition, findings suggest that certain absences, such as traditional discourses of masculinity, also facilitate a more accepting school for LGBT students. However, the study also finds that such factors are complexly interwoven and as a result, causality is difficult to determine.